Public smoking ban and socioeconomic inequalities in smoking prevalence and cessation: a cross-sectional population-based study in Geneva, Switzerland (1995–2014). Issue 6 (26th January 2018) - Sandoval, José Luis; Leão, Teresa; Cullati, Stéphane; Theler, Jean-Marc; Joost, Stéphane; Humair, Jean-Paul; Gaspoz, Jean-Michel; Guessous, Idris
Abstract : Introduction: Smoking bans were suggested to reduce smoking prevalence and increase quit ratio but their equity impact remains unclear. We aimed to characterise the socioeconomic status (SES)-related inequalities in smoking prevalence and quit ratio before and after the implementation of a public smoking ban. Methods: We included data from 17 544 participants in the population-based cross-sectional Bus Santé study in Geneva, Switzerland, between 1995 and 2014. We considered educational attainment (primary, secondary and tertiary) as a SES indicator. Outcomes were smoking prevalence (proportion of current smokers) and quit ratio (ex-smokers to ever-smokers ratio). We used segmented linear regression to assess the overall impact of smoking ban on outcome trends. We calculated the relative (RII) and slope (SII, absolute difference) indexes of inequality, quantifying disparities between educational groups in outcomes overall (1995–2014), before and after ban implementation (November 2009). Results: Least educated participants displayed higher smoking prevalence (RII=2.04, P<0.001; SII=0.15, P<0.001) and lower quit ratio (RII=0.73, P<0.001; SII=−0.18, P<0.001). As in other studies, smoking ban implementation coincided with a temporary reduction of smoking prevalence (P=0.003) and increase in quit ratio (P=0.02), with a progressive return to preban levels. Inequalities increased (P<0.05) in relative terms for smoking prevalence (RIIbefore =1.84, P<0.001 and RIIafter =3.01, P<0.001) and absolute terms for both outcomes (smoking prevalence: SIIbefore =0.14, P<0.001 and SIIafter =0.19, P<0.001; quit ratio: SIIbefore =−0.15, P<0.001 and SIIafter =−0.27, P<0.001). Conclusions: Implementation of a public smoking ban coincided with a short-lived decrease in smoking prevalence and increase in quit ratio but also with a widening in SES inequalities in smoking-related outcomes.